The Effect of Online Project Based Learning on Students’ Character - Krisna Merdekawati; Umi Marifatul Ngilmi; Widinda Normalia Arlianty (Universitas Islam Indonesia, 2022)
The Covid-19 pandemic that emerged in early 2020, has had a very significant impact on various sectors, including education. Each country shifts learning activities at various levels from face-to-face (offline) to online learning. Achieving competences according to the high school chemistry curriculum is quite difficult to do through online learning, especially for skills and attitudes competency aspects. Chemistry learning during pandemic tended to focus on attaining the knowledge aspect. It needs attention, lest during the pandemic, there will be a degradation of students’ character. It is necessary to design chemistry learning that can facilitate the development of students’ character. One of the efforts that can be done is implementing a variety of online learning models. Project based learning can be an alternative strategy to facilitate the development of students’ character. It is necessary to conduct a study to determine the implementation strategy and impact of project based online learning, because it is not easy to apply the syntax in online learning. The purpose of this study was to investigate the effects of project based online learning on students’ character. The study was a quasi-experimental, with posttest only design. The research population was students of class XI of a public high school in Sleman Regency. The research sample was determined by using purposive sampling technique. The data collection instrument was a questionnaire. The data analysis technique used the independent sample T-test. Based on the research data, it is concluded that there is no difference on students’ character between the implementation of project based online learning and conventional online learning. Keywords: online learning, project-based learning, prophetic character